Limits of Econometrics - David A. Freedman (International Econometric Review (IER), 2009)
In the social and behavioral sciences, far-reaching claims are often made for the superiority of advanced quantitative methods by those who manage to ignore the far-reaching assumptions behind the models. In section 2, we see there was considerable skepticism about disentangling causal processes by statistical modeling. Freedman (2005) examined several well-known modeling exercises, and discovered good reasons for skepticism. Some kinds of problems may yield to sophisticated statistical technique; others will not. The goal of empirical research is or should be to increase our understanding of the phenomena, rather than displaying our mastery of technique.
Keywords: 330